Antioxidant capacity and total phenolic content of air-dried cape gooseberry (physalis peruviana l.) at different ripeness stages (2014)
Because the use of drying at high temperatures might negatively affect the functional properties of fruits, the effect of air-drying at 60°C on the total phenolic content (TPC) and antioxidant capacity (AOC) of cape gooseberry fruit was evaluated at three ripeness stages. The AOC was evaluated with 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing ability of plasma (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH), and β-carotene-linoleate assays. The TPC and AOC increased in the fresh fruit as the ripeness stage increased. The TPC increased from 401.8±19.8 to 569.3±22.3 mg GAE/100 g dry weight (DW). The AOC values obtained with ABTS in the fresh fruit (ranging from 79.4±4.5 to 132.7±12.9 µmol trolox/g fruit DW) were comparable to those obtained with FRAP (ranging from 82.9±16.3 to 153.9±31.7 µmol trolox/g fruit DW). The values assessed with DPPH ranged from 21.0±3.2 to 34.1±5.1 µmol trolox/g fruit DW. The β-carotene-linoleate assay gave values ranging from 5.8±1.1 to 12.7±2.0 µmol α-tocoferol/g fruit DW. Air-drying the cape gooseberry fruit had a small influence on the TPC. The air-dried fruit had AOC values ranging from 27 to 164% of the value of the fresh fruit. While the ABTS assay produced higher values in the air-dried fruit than in the fresh fruit, the FRAP, DPPH, and β-carotene-linoleate assays resulted in lower values in the air-dried fruit.